Elemental composition of total suspended particulate matter in Kuala Lumpur - A preliminary survey - Mohd. Yusoff, Mohd. Rashid (1986)
Eighteen samples of ambient 24-hr average total suspended particulate matter were collected at Universiti Teknologi Malaysia sampling station. A total of 25 trace-elements (Al, Ag, As, Au, Ba, Br, Ca, Cd, Co, Cr, Cu, Dy, Eu, Fe, La, Mg, Mn, Ni, Pb, Sb, Sc, Sm, Ti, V and Zn) were determined from the samples using instrumental neutral activation analysis and atomic absorption spectrophotometry techniques. The use of pairwise correlation statistic and enrichment factors were presented to identify sources. It was demonstrated that the particulate can be related into two specific source categories: soil derived (Al, Au, Ba, Ca, Cr, Cu, Dy, Eu, Fe, La, Mg, Mn, Sc, Sm, Ti, and V) and anthropogenic sources (Ag, As, Br, Cd, Co, Ni, Pb, Sb, and Zn). Pb and Br were mainly due to automobile exhausts emission.